2022
DOI: 10.1038/s41477-022-01136-8
|View full text |Cite
|
Sign up to set email alerts
|

Noise reduction by upstream open reading frames

Abstract: Gene expression is prone to burst production, making it a highly noisy process that requires additional controls. Upstream open reading frames (uORFs) are widely present in the 5′ leader sequences of 30–50% of eukaryotic messenger RNAs1–3. The translation of uORFs can repress the translation efficiency of the downstream main coding sequences. Whether the low translation efficiency leads to a different variation, or noise, in gene expression has not been investigated, nor has the direct biological impact of uOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Even though the variant in 5’UTR might affect the binding of a transcription factor 41 , the contribution of transcriptional regulation could be minor in our study because the causal SNP changes the length of a uORF, which often functions at the post-transcriptional and translational levels 42 . uORF is known to play instrumental roles in translation control of the downstream main ORF in a broad spectrum of eukaryotes 43 . Furthermore, when a uORF is translated, a long 3’UTR downstream of the uORF may activate nonsense-mediated decay to affect mRNA stability and thus steady-state mRNA levels 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though the variant in 5’UTR might affect the binding of a transcription factor 41 , the contribution of transcriptional regulation could be minor in our study because the causal SNP changes the length of a uORF, which often functions at the post-transcriptional and translational levels 42 . uORF is known to play instrumental roles in translation control of the downstream main ORF in a broad spectrum of eukaryotes 43 . Furthermore, when a uORF is translated, a long 3’UTR downstream of the uORF may activate nonsense-mediated decay to affect mRNA stability and thus steady-state mRNA levels 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of mouse and human mRNAs contain uORFs, and uORFs are associated with widespread translational repression (Johnstone et al, 2016). Thus, uORF translation suppression may constitutively lower the abundance of circadian proteins or provide a post-transcriptional foothold to adjust protein abundance by altering the activities of ribosome reinitiation factors (Bohlen et al, 2020; Morris and Geballe, 2000; Schleich et al, 2014), and mutagenesis of uORFs have been shown to alter rhythmicity in other circadian systems (Diernfellner et al, 2005; Wu et al, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…Thus, uORF-mediated translation suppression may constitutively suppress the abundance of circadian proteins or provide a post-transcriptional foothold to adjust protein abundance by altering the activities of ribosome reinitiation factors (37)(38)(39). Moreover, mutagenesis of uORFs have been shown to alter rhythmicity in other circadian systems (40,41). Not all ribosome binding in 5'UTRs was associated with uORFs, and we observed extensive ribosome binding in areas without an apparent uORF for Cry1, Nr1d1, Clock, Dbp, and Per3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main protein expression in uORF-bearing transcripts requires leaky scanning across the uORF start site(s) or reinitiation of ribosomes after translating the uORF followed by reloading with essential co-factors [ 71 , 72 ]. Upstream ORFs play critical roles in diverse cellular programs including the integrated stress response (ISR) [ 71 , 73 ], circadian timekeeping [ 74 , 75 ], and microtubule organization [ 76 ]. Translational regulation allows for immediate responses to changing environmental conditions, bypassing the need for time-consuming transcription of new mRNAs.…”
Section: Functional Implications Of Uorf-encoded Upeptides and Hla Ul...mentioning
confidence: 99%